Advances in Plant Alkaloid Research (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Plant alkaloids are critical components of modern medicine and pharmaceuticals. These compounds are also becoming increasingly important for industrial uses as part of the green chemistry revolution. This Special Issue will focus on the molecular advances being made in understanding how such a large and diverse class of compounds are made by plants and how metabolic engineering advances are increasing the overall yield of crucial precursors.